1988
DOI: 10.1177/154079698801300104
|View full text |Cite
|
Sign up to set email alerts
|

System of Least Prompts: A Literature Review of Procedural Parameters

Abstract: This manuscript describes an instructional strategy, system of least prompts, and reviews the use of the procedure in the applied research literature. The literature is analyzed in terms of the populations for which the procedure has been used, the type of skills that have been taught with the procedure, and the results when the procedure was employed. The literature also is described in terms of previously identified parameters of the system of least prompts including (a) the number and type of prompts includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 30 publications
0
75
0
Order By: Relevance
“…Constant time delay (CTD) was used in the largest number of studies. The time delay, simultaneous prompting, and the system of least prompts procedures are quite effective in 1:1 instruction (Doyle et al, 1988;Morse & Schuster, 2004;Wolery, Holcombe, et al, 1992), and these results suggest that they are effective in smallgroup arrangements as well. Recently, in three studies, these prompting strategies were applied in SGDI using electronic technologies such as SMART Boards (Campbell & Mechling, 2009;Mechling, Gast, & Krupa, 2007;Mechling, Gast, & Thompson, 2008).…”
Section: Under What Conditions Was Prompting In Sgdi Studied?mentioning
confidence: 84%
See 1 more Smart Citation
“…Constant time delay (CTD) was used in the largest number of studies. The time delay, simultaneous prompting, and the system of least prompts procedures are quite effective in 1:1 instruction (Doyle et al, 1988;Morse & Schuster, 2004;Wolery, Holcombe, et al, 1992), and these results suggest that they are effective in smallgroup arrangements as well. Recently, in three studies, these prompting strategies were applied in SGDI using electronic technologies such as SMART Boards (Campbell & Mechling, 2009;Mechling, Gast, & Krupa, 2007;Mechling, Gast, & Thompson, 2008).…”
Section: Under What Conditions Was Prompting In Sgdi Studied?mentioning
confidence: 84%
“…These procedures include constant time delay, progressive time delay, simultaneous prompting, the system of least prompts, most to least prompting, graduated guidance, and error correction . The effectiveness of prompting procedures has been experimentally demonstrated in a number of studies (for reviews, see Doyle, Wolery, Ault, & Gast, 1988;Schuster et al, 1998;Wolery, Holcombe, et al, 1992). Some experimental evaluations have shown that, at least in some circumstances, one prompting procedure may be more efficient than another (e.g., Riesen, McDonnell, Johnson, Polychronis, & Jameson, 2003;Schuster, Griffen, & Wolery, 1992), but all of these procedures have been shown to be effective for a variety of students with and without disabilities .…”
mentioning
confidence: 99%
“…This strategy is an excellent way for a teacher or clinician to identify the least intrusive prompt to use with a student. It should also be noted that the system of least prompts is an excellent teaching strategy in its own right with a long history of effectiveness with a wide range of learners and tasks (Doyle, Wolery, Ault, & Gast, 1988). Third, investigators incorporated a means by which learners could demonstrate independent performance each session by the including a daily probe session.…”
Section: Authors' Conclusionmentioning
confidence: 99%
“…Reinforcement is provided for correct Skills Loosen tape tabs at sides of diaper Pull diaper forward Remove diaper Position diaper between legs Close diaper tape securely on each side Wash hands prior to catheterization Cleanse diaper area Cleanse penile area after urination Wash hands after catheterization Insert lubricated catheter into penis until urine flows Hold catheter in place until urine flow stops with abdominal muscles to maximize urine flow >ve catheter when urine flow stops responses. Incorrect responses or responses that are less than accurate result in the delivery of a more intrusive level of prompt (Doyle, Wolery, Ault, & Gast, 1988). The process continues until the learner demonstrates an accurate response or until all of the prompts in the hierarchy have been delivered.…”
Section: Training Proceduresmentioning
confidence: 97%